Germinação e cultivo in vitro de Calendula officinalis L. - Bevilacqua, Caroline Borges (2009)
The objective this present study was developed a protocol of surface disinfection of marigold seeds; through immersion of seeds in etanol solution 70%, for 30 s. followed by different times of immersion in 2,5% sodium hypoclorite solution (0, 10, 20 e 30 min) plus one drop of detergent commercial; selected a methodology by break barries to germination of marigold seeds of calendula in vitro (immersion in sulfuric acid absolute during 5 min; immersion in cloridric acid absolute during 5 min; removal of tegument and imbibiton of seeds in water destilled, during 12 h; imbibiton of seeds in water destilled, during 12 h; control). Beyond tested growth regulators concentrations (absence of growth regulators; 0,01 mg L-1 of ANA; 0,5 mg L-1 of BAP; 1 mg L-1 of BAP; 1,5 mg L-1 of BAP, in a factorial model) what induce the induction of calli in leaf segments from ex vitro and in vitro culture; evaluate the regeneration potential in vitro culture from marigold seeds in presence and absence of growth regulators (absence of growth regulators; 0,5 μ mol of ANA; 2μ mol of BAP; 3μ mol of BAP; 4 μ mol of BAP; 5 μ mol of BAP; 6μ mol of BAP; 7μ mol of BAP, in a factorial model); evaluate the influences of in vitro culture time in calli regeneration formed under growth regulators concentrations and different concentration of growth regulators (absence of growth regulators; 2μ mol of BAP and 0,5 μ mol of ANA; 5 μ mol of BAP and 0,5 μ mol of ANA; 6 μ mol of BAP and 0,5 μ mol of ANA; 7μ mol de BAP and 0,5 μ mol of ANA; containing old calli; containing young calli, in a factorial model) in regeneration and type formed. Verified was that the immersion in 2,5% sodium hypoclorite solution for 30 min coupled with the removal of tegument promoted the in vitro germination of marigold seeds and making a surface disinfection satisfactory of seeds; not is necessary of supplementation with cytokinins to promote the rhizogenesis in marigold; is necessary the addiction of BAP the nutrient medium to occur calogenesis in leaf segments from the in vitro culture and in seeds, need to be great concentration that growth regulator if the culture is made in the ANA presence; for calogenesis in leaf segments coming of ex vitro culture, not is necessary increase the BAP concentration in ANA presence; for regeneration of aerial parts from seeds not is necessary the BAP supplementation or ANA; for regeneration of roots from seeds not is necessary BAP presence or ANA, however with ANA addiction become necessary BAP supplementation; the calogenesis is favored the use of BAP; calli more tumid were verified in growth regulators presence; young calli in ANA and BAP absence and presence induced formation of spongy calli and of green calli; young calli are more efficient to regenerate aerial parts.